EPILOGUE: Why John Laurance Matters. (Transactions of the American Philosophical Society, 2019)
The article offers information related to the impact of John Laurance, former U. S. Representative on the history of U.S. politics. Topics discussed include role of senators in Second World War; role of foreign-born citizens federal government of 18th century; and establishment of precedent for prosecuting personally at the nighest-profile trials by Laurance.